INVESTIGATION MEMORY LEARNING STRATEGY USED BY STUDENTS’ VOCATIONAL SCHOOL AS ENGLISH FOREIGN LANGUAGE - Wardhani, Ryda Kusuma; Susanto, Dias Andris (PRIMER : Jurnal Ilmiah Multidisiplin, 2023)
The focus of this study was to determine which memory strategy was more frequently used by students at SMK N 4 Semarang. This study involved 35 students from class 12 building engineering 3. A descriptive qualitative technique with a questionnaire survey was used to collect data from 35 students of SMK N 4 Semarang who completed the first nine questions of the Strategy Inventory for Language Learning (SILL) questionnaire and a Background Characteristics survey. According to Miles dan Hubermen (1994), believes that in qualitative data analysis, actions are carried out interactively and constantly until the data is saturated. The absence of new data or information is a measure of data saturation. The research process includes three concurrent streams of activities: data reduction, data display, and drawing conclusions/verification. The outcomes of the study demonstrate that how English is used in practice influences how well it is acquired. The findings showed that memory strategy most frequently used by the students was I use rhymes to remember new English words or I physically act out new English words. As a result, teachers should consider this and engage with students to encourage and expand understanding of the benefits of using memory strategies successfully when studying English as a foreign language.